2002
DOI: 10.1111/j.1095-8649.2002.tb01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in food intake within groups of juvenile perch

Abstract: The coefficient of variation of individual food intake was large in small groups of young-ofthe-year perch Perca fluviatilis (45-60 mm L T ) and smaller when fish that were given the same feeding rank were placed together. No aggressive interactions were detected during feeding. 2002 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…This is in agreement with previous results on food intake within groups of 0+ perch (Staffan et al 2002). Regardless of fish feeding in groups of three, or, individually, intake rate of dominants exceeded that of subordinates (in groups: dominants 15.04 ± 2.26 daphnia fish )1 min )1 , subordinates 4.11 ± 0.86; individually: dominants 17.10 ± 3.05 daphnia fish )1 min )1 , subordinates 4.20 ± 0.72) (Two way repeated measures ANO-VA: effect of fish status -F=87.78, p < 0.001; effect of foraging group -F=0.45, p = 0.510; no interaction between factors).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with previous results on food intake within groups of 0+ perch (Staffan et al 2002). Regardless of fish feeding in groups of three, or, individually, intake rate of dominants exceeded that of subordinates (in groups: dominants 15.04 ± 2.26 daphnia fish )1 min )1 , subordinates 4.11 ± 0.86; individually: dominants 17.10 ± 3.05 daphnia fish )1 min )1 , subordinates 4.20 ± 0.72) (Two way repeated measures ANO-VA: effect of fish status -F=87.78, p < 0.001; effect of foraging group -F=0.45, p = 0.510; no interaction between factors).…”
Section: Resultssupporting
confidence: 94%
“…Dominantsubordinate relationships allow the dominant individuals to obtain a disproportionally bigger share of contestable resources, including not only food, but also a refuge from predators (Grant 1997), which is especially important for juvenile fish. Staffan et al (2002) found variation in food intake within groups of juvenile perch to be considerable, but foraging was not accompanied by any aggressive interactions. The aim of this study was to test the hypothesis that interference competition among 0+ perch might appear in structured habitats when shelter is a limited resource.…”
Section: Introductionmentioning
confidence: 89%
“…It is, for example, common that dominance structures develop given high enough levels of intraspeciWc competition (Whiteman and Cote 2004) which, in turn, can result in increased size variation as a result of dominant individuals obtaining a disproportionate share of the resources (Borowsky 1973;Grant 1993). It has, furthermore, been shown that food intake can also be highly variable among similarly sized individuals within groups of YOY perch (StaVan et al 2002). Given that young perch is a shoaling Wsh species when feeding on zooplankton (Craig 2000), individual diVerences in feeding rates not related to size-dependent exploitative interactions may also have contributed to observed diVerences in growth rates among individuals in our experiment.…”
Section: Discussionmentioning
confidence: 96%
“…Aggression is also associated with social position or rank ( Mazur & Booth, 1998 ; Staffan, Magnhagen & Alanärä, 2002 ). For example, an albino female vampire bat Desmondus rotundus bred with pigmented individuals hold the lowest social position ( Uieda, 2001 ).…”
Section: Discussionmentioning
confidence: 99%